Photocatalysis of functionalised 3D printed cementitious materials - Zadeh, Behzad Zahabi (2023)
The main objective of this study was to evaluate the photocatalytic behaviour of 3D printed cementitious mortars that were functionalised with TiO2 nanoparticles. This study is one of the few available regarding functionalisation of 3D concrete printing (3DCP) with photocatalytic properties. Despite the fact 3DCP research is swiftly growing, it is still necessary further investigation to fully understand these materials’ physicochemical and mechanical properties, which will influence the functionalised properties of the composite. Due to the freeform nature of the 3DCP there are no moulds, therefore the functionalisation through coating can be performed in a much earlier stage than in conventional moulded concrete. The developed smart 3D printed concrete could promote the photodegradation of pollutants for self-cleaning and air purification. In particular, this study investigated the effect of two parameters on photocatalytic behaviour: light power intensity and the coating rate of nano-TiO2 particles. Surface coating was adopted as the functionalisation method, and the Rhodamine B dye degradation efficiency was used as an indicator to evaluate the photocatalytic behaviour. Additionally, the surface roughness and microstructure of the 3D printed cementitious mortar specimens were assessed to distinguish between the reference and TiO2 coated series. Scanning electron microscopy (SEM), X-ray Energy dispersive spectroscopy (EDS), and X-ray diffraction (XRD) crystallography were carried out as three techniques to evaluate the morphology, composition, and microstructure of the specimens, respectively. The results indicated successful activation of catalyst particles under illumination, where higher light power intensity increased the degradation efficiency. Furthermore, dye degradation efficiency increased with increasing coating rates of nano-TiO2 particles on the surface of the specimens. The roughness of the 3D printed specimens’ surface was sufficient for settling the nano-TiO2 particles. Finally, microscopy results confirmed the presence and suitable distribution of the nano-TiO2 particles on the surface of the coated specimens.